Wednesday

April 23, 2014

April 23, 2014

Posted by **Jo** on Tuesday, October 25, 2011 at 12:04am.

- Calculus -
**Steve**, Tuesday, October 25, 2011 at 5:12amUse implicit differentiation:

xy^3 / (1+y^2) = 8/5

(y^3 + 3xy^2 y')(1+y^2) - xy^3 (2yy') = 0

It's all over (1+y^2)^2, but that can be ignored, since it's never 0.

y'(3xy^2 + 3xy^4 - 2xy^4) = -y^3(1 + y^2)

y' = -y^3 (1+y^2)/(3xy^2 + xy^4)

= -y/x * (1+y^2)/(3 + y^2)

Take it from there.

**Related Questions**

calculus - A particle is moving along the curve below. y = sqrt(x) As the ...

Calculus - A particle is moving along the curve . As the particle passes through...

Calculus - A particle is moving along the curve . As the particle passes through...

Calculus - A particle is moving along the curve . As the particle passes through...

Calculus - A particle is moving along the curve y = 2 √{3 x + 7}. As the ...

Calculus - A particle is moving along the curve y = 2 √{3 x + 7}. As the ...

Calculus - A particle is moving along the curve y = 2 √{3 x + 7}. As the ...

Calculus 1 - A particle is moving along the curve y= 4 \sqrt{3 x + 1}. As the ...

calculus - A particle is moving along the curve y=5sqrt(3x+1). As the particle ...

calculus - A particle is moving along the curve y=4((3x+1)^.5). As the particle ...